Hemispherical Low Blow Impact Treatment Spot-welded Joint - Salleh, Z.; R. N. M.Masdek, N.; M. Taib, Y.; A. Ghazali, F. (International Journal of Engineering and Technology, 2018)
Resistance spot welding (RSW) is one of the latest techniques to join sheet metals together by utilizing both current and pressure through specific or localized area. In this study, the effect of tensile shear on the resistance spot welding after the low blow impact treatment of low carbon steel sheet with 1.2 mm thickness, using a hemispherical head are investigated. The microstructures of the welded parts were also examined. In the automotive industry, this technique is widely used due to several advantages. In addition, the hardness of the samples was also evaluated. Before conducting the experiment, the samples were examined using a spectrometer in order to identify the essential elements in the sample. Tensile shear test and hardness test were conducted to investigate the mechanical properties of the steel with and without post welding treatment that is the low blow impact treatment (LBIT) by using a hemispherical head. Based on the results obtained, it was found that samples that have been treated with LBIT of 20 Joule energy level had the highest maximum load, in which it can withstand 5.744 kN load before failure. This suggests that the hemispherical LBIT on the spot welded has a high potential technique that could be used to improve the mechanical properties of the join.Â Â